Patterns and outcomes of neurosurgery in England over a five-year period: A national retrospective cohort study. (March 2022) - Wahba, Adam J.; Cromwell, David A.; Hutchinson, Peter J.; Mathew, Ryan K.; Phillips, Nick
Abstract: Background: Neurosurgical practice has seen major changes over several decades. There are no recent evaluations of national neurosurgical practice. The aim of this observational study was to describe neurosurgical practice in England and to use outcomes to assess and benchmark the quality of care in neurosurgery. Material and methods: This national retrospective cohort study analysed Hospital Episode Statistics (HES) data from April 2013 to March 2018 for all adult admissions with a specialty code for neurosurgery. The epidemiology of patients and RCS Charlson comorbidities were derived and procedure incidence rates per 100, 000 person-years calculated. Post-operative outcomes for elective and non-elective patients included: median length of stay, the proportion of patients requiring additional inpatient neurosurgical procedures, the proportion of patients discharged to their usual address, and in-hospital mortality rates. Results: During the 5-year study period, there were 371, 418 admissions to neurosurgery. The proportion of admissions involving a neurosurgical procedure was 77.3% (n = 287, 077). Of these, 45% were for cranial surgery and 37% for spinal. Overall, 68.3% were elective procedures. The incidence rates of most procedures were low (<20 per 100, 000 person-years). Following elective neurosurgical procedures, in-hospital mortality rates for cranial and spinal surgery were 0.5% (95% CI, 0.5–0.6) and 0.1% (95% CI, 0.04–0.1), respectively. After non-elective neurosurgery, mortality rates were 7.4% (95% CI, 7.2–7.6) and 1.3% (95% CI, 1.2–1.5) for cranial and spinal surgery, respectively. Approximately 1 in 4 patients had additional procedures following non-elective cranial surgery (24%; 95% CI, 23.6–24.3). Outcomes were highly variable across different subspecialty areas. Conclusions: The incidence rates of neurosurgical procedures are low within England, and neurosurgical units have a high volume of non-surgical admissions. In-hospital mortality rates after elective neurosurgery are low but there may be opportunities for quality improvement programmes to improve outcomes for non-elective surgery as well as ensuring equitable access to treatment. Highlights: This study used Hospital Episode Statistics to describe neurosurgical practice in England. Neurosurgical procedure incidence rates are low within England. In-hospital elective mortality rates are low. Outcomes following non-elective neurosurgery are worse than elective neurosurgery. The findings provide baseline outcomes for benchmarking of quality of care.